THE MINIMUM WAGE AND ECONOMIC GROWTH. ANALYSIS IN THE CASE OF ROMANIA - Nicoleta MIHĂILĂ (Financial Studies, 2022)
There are theoretical and empirical studies that highlight a variety of determinants of economic growth, including investments, physical capital accumulation, human capital, innovation, political and legal institutions, macroeconomic conditions etc. The purpose of our paper is to determine the extent to which the evolution of the minimum wage has influenced the economic growth in Romania in the period 2007-2021, the objectives pursued being the definition of economic growth and the method of measuring it, the evolution of the minimum wage in the period mentioned above, as well as determining the effects the minimum wage on some economic indicators (consumption, GDP/capita). In this sense, we use an empirical and descriptive methodology, by referring to statistical data and bibliographic references from national and international literature.